Предмет: Химия,
автор: Superbrain1n
Fe>Fe2O3> >Fe(OH)3>Fe(NO3)3
Ответы
Автор ответа:
0
4Fe + 3O2 → 2Fe2O3
Fe2O3+6NaOH → 2Fe(OH)3 + 3Na2O
Fe(OH)3 + 3HNO3 → Fe(NO3)3 + 3H2O
Fe2O3+6NaOH → 2Fe(OH)3 + 3Na2O
Fe(OH)3 + 3HNO3 → Fe(NO3)3 + 3H2O
Автор ответа:
0
4Fe + 3O₂(изб.) = 2Fe₂O₃
Fe₂O₃ + 6HCl = 2FeCl₃ + 3H₂O
FeCl₃ + 3NaOH = Fe(OH)₃↓ + 3NaCl
Fe(OH)₃ + 3HNO₃ = Fe(NO₃)₃ + 3H₂O
Fe₂O₃ + 6HCl = 2FeCl₃ + 3H₂O
FeCl₃ + 3NaOH = Fe(OH)₃↓ + 3NaCl
Fe(OH)₃ + 3HNO₃ = Fe(NO₃)₃ + 3H₂O
Похожие вопросы
Предмет: История,
автор: dubynad0804
Предмет: Геометрия,
автор: pasapalamarcuk91
Предмет: Русский язык,
автор: nodirovichi
Предмет: Математика,
автор: denissid777